Otroške igre v novogvinejski skupnosti - Telban, Borut (Etnolog. Nova vrsta (Ljubljana), 2007)
While Ambonwari children from the East Sepik Province, Papua New Guinea, are growing up into their intimate environment (natural, social, cultural), they are simultaneously infl uencing and creating it. One of the ways of creating of their life-world is hidden in their playing. On the one hand children are through playing introduced into culturally specifi c and socially expected roles of men and women, which are based on the relationship between brother and sister. On the other hand children soon learn that happenings in their natural environment are not independent from humans and that they can infl uence and create them. The latter becomes most evident in two collective games: catćs cradle and the game of spinning-tops.
Keywords: Nova Gvineja; child; otroci; igre; odraščanje; zibka